Experiences with Supporting Teachers with Scholarship of Teaching and Learning at a Research-Intensive University: Lessons Learned - Meijerman, Irma; Kirschner, Femke; Prins, Frans (Teaching and Learning Inquiry, 2023)
Scholarship of Teaching and Learning (SoTL) is a fast-maturing field of study within many research-intensive universities. SoTL improves the quality of teaching, the professional development of teachers, and the recognition and appreciation of education. To encourage SoTL, it is important to know how to support teachers. This study describes two pilot initiatives with the goal to encourage and support teachers at a research-intensive university with their first SoTL project. In both pilots, a community of practice (CoP) approach was used. The experiences with the pilots were investigated with questionnaires and interviews. Based on the feedback of participants, albeit with some caution because of the relatively small sample size of this study, suggestions for future initiatives that support teachers new to SoTL at research-intensive institutes are: 1) the use of a combination of a CoP and individual guidance by experienced SoTL facilitators; 2) the creation of opportunities for formal and informal interaction to strengthen the CoP; 3) encouraging participants to work together on (shared) aligned projects; 4) the provision of structured course elements with guided discussions; 5) the provision of theoretical support regarding the principles of SoTL, for example, finding and interpreting literature, formulating a research question, and choosing the research methodology; 6) structure the inclusion of students’ participations, perspectives, and roles in SoTL; 7) some form of obligation, such as an official status of the initiative; and 8) institutional support, such as providing recognition, time, and financial support. The lessons learned in this study have relevance for all universities seeking to embrace, encourage, and support SoTL, especially for those initiating their first SoTL-supporting activities. Click here to read the corresponding ISSOTL blog post.